Student Perceptions in Measuring Teaching Behavior Across Six Countries: A Multi-Group Confirmatory Factor Analysis Approach to Measurement Invariance - André, Stéfanie; Maulana, Ridwan; Helms-Lorenz, Michelle; Telli, Sibel; Chun, Seyeoung; Fernández-García, Carmen-María; de Jager, Thelma; Irnidayanti, Yulia; Inda-Caro, Mercedes; Lee, Okhwa; Safrina, Rien; Coetzee, Thys; et al. (Frontiers in Psychology, 2020)
The purpose of this study is to examine measurement invariance of scoring of teaching behavior, as perceived by students, across six cultural contexts (Netherlands, Spain, Turkey, South Africa, South Korea, and Indonesia). It also aims to compare perceived teaching behavior across the six countries based on a uniform student measure. Results from multi-group confirmatory factor analyses (MGCFA) showed perceived teaching behavior in the six countries to be adequately invariant. Perceived teaching behavior was the highest in South Korea and the lowest in Indonesia. The findings provide new insights into the relevance and differences of teaching behavior across cultural contexts.